STUDENTS’ ATTITUDE TOWARDS ENGLISH ACTIVE USE OF ENGLISH LANGUAGE EDUCATION STUDY PROGRAM AND ENGLISH LETTERS STUDY PROGRAM AT KHAIRUN UNIVERSITY - Asrul Asrul (Universitas Khairun, 2018)
This research aims to find students’ attitude towards English active use of English language education study program and English letters study program at Khairun University in classroom. Method of collecting data uses qualitative research. Instrument in this research uses questionnaires. The questionnaires are consisting of 40 items. Data analysis techniques used descriptive statistics. Subject of this research consists of 51 students and purposive samples. The result in this research indicates that the students’ attitude of English Language Education Study Program and English Letters Study Program at Khairun University in classroom obtained Agree 41.76%, and then followed by Disagree 26.13%, Strongly Agree 20.29%, Strongly Disagree 6.96%, and No Attitude 4, 85%. This research recommended for lecturer to encourage students using English in the classroom actively